High-thermal-conductivity nylon composite material and preparation method thereof
Through solution plasma surface treatment and silane coupling agent modification of boron nitride of siloxane and aziridine, the problems of complex preparation process of existing thermally conductive nylon materials and poor interfacial binding force are solved, and high thermal conductivity and mechanics are achieved The performance improvement simplifies the process and reduces the amount of boron nitride.
Patent Information
- Application Number
- CN202310821676.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2025-01-07
AI Technical Summary
The existing thermally conductive nylon materials have complex preparation processes and poor interface bonding forces, resulting in insufficient thermal and mechanical properties, and the strong oxidative chemical reagents used are unfriendly to the environment.
Modify boron nitride by solution plasma surface treatment and siloxane and aziridine silane coupling agent to improve its compatibility and dispersion with nylon, combine BN with nylon through chemical bonding, simplify the preparation process and Reduce the amount of boron nitride.
A high thermal conductivity nylon composite material with simple operation and large-scale preparation is realized, which improves the compatibility and dispersion of boron nitride and nylon, reduces the amount of BN, and obtains excellent thermal conductivity and mechanical properties.
Smart Images

Figure BDA0004323643710000131 
Figure HDA0004323643720000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite materials, and in particular relates to a high thermal conductivity nylon composite material and a preparation method thereof. Background Art
[0002] With the development of miniaturization, integration, high speed and high frequency of electronic components, their internal energy density has increased dramatically and the heat generation has increased significantly. In order to maintain their operational stability and safety, it is crucial to design and prepare packaging materials with excellent thermal management performance. Polymers and their composite materials have become the main substrates and packaging materials for electronic components and other products due to their easy processing, corrosion resistance and low cost. Among them, nylon has lower cost, better thermoplastic processing performance, and stronger bonding strength with solder, making it a more important matrix material. However, the thermal conductivity of nylon itself cannot meet the thermal management requirements of electronic components, so it needs to be filled and modified.
[0003] Hexagonal boron nitride, with its unique two-dimensional flake morphology and excellent intrinsic thermal conductivity, makes it a highly efficient insulating and thermally conductive filler. The thermal conductivity of a single layer of h-BN is close to 1700-2000W / (m·K). In addition, h-BN is also resistant to thermal vibration, oxidation, high resistivity, high dielectric properties, low density, and good processability. These characteristics make h-BN widely used in insulation, thermal conductivity, lubrication, temperature resistance, microwave shielding and other fields.
[0004] However, h-BN does not have any functional groups or active sites that can be used for bonding modification, which makes it difficult to disperse in resins and solvents. The main method to improve the dispersibility of h-BN is to functionalize it, usually by hydroxylating it first. However, the hydroxylation modification method is generally implemented under special conditions such as strong mechanical force, strong acid and alkali or strong oxidation. These methods have the disadvantages of being time-consuming, complicated to operate, and using strong oxidizing chemical reagents that are environmentally unfriendly and highly toxic. The plasma modification method is more gentle, can be prepared in large quantities with industrial feasibility, and can guarantee a high hydroxylation yield, which is more conducive to subsequent further modification. In subsequent modifications, silane coupling agents are often used to couple inorganic substances with organic polymers, but general silane coupling agents have poor compatibility with nylon matrices, resulting in the need to use a high content of BN to achieve the required thermal conductivity effect.
[0005] In summary, existing thermal conductive nylon materials still have problems such as complex preparation process and poor interface bonding strength. Summary of the invention
[0006] In view of the above problems existing in the prior art, one of the purposes of the present invention is to provide a high thermal conductivity nylon composite material, which overcomes the problems existing in the existing materials, has the advantages of simple operation, large-scale preparation, high degree of hydroxylation, and the special coupling agent used can greatly improve the compatibility and dispersibility of boron nitride and nylon matrix, which can reduce the amount of boron nitride used and obtain excellent thermal conductivity and mechanical properties.
[0007] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0008] A high thermal conductivity nylon composite material, the material comprising modified boron nitride and nylon, the mass ratio of nylon to modified boron nitride being 95:5-60:40; wherein the modified boron nitride is boron nitride surface-treated by solution plasma and modified by a silane coupling agent containing siloxane and aziridine; preferably, the raw material boron nitride is hexagonal boron nitride; wherein the nylon is one or more of nylon 6, nylon 66, nylon 610, nylon 1010, nylon 11, nylon 12, nylon 612, nylon 46, nylon 7, nylon 9, and nylon 13, preferably nylon 6 and / or nylon 66.
[0009] The present invention uses solution plasma to treat the surface of h-BN, which can effectively increase the number of hydroxyl groups on its surface, and then reacts with an aziridine compound containing a siloxane group to obtain BN containing an aziridine group on the surface. The aziridine group on the surface of BN undergoes a ring-opening reaction with the carboxyl group of nylon, so that BN and nylon are combined in the form of a chemical bond, which can improve the interface bonding between BN and the nylon matrix to make it have better compatibility, and also make BN have better dispersibility. Among them, conventional boron nitride can obtain better effects, and nano hexagonal boron nitride can obtain better effects.
[0010] Another object of the present invention is to provide a method for preparing modified boron nitride.
[0011] A preparation method of the modified boron nitride is disclosed. The modified boron nitride is prepared by two steps, one of which is solution plasma surface treatment and the other is modification with a silane coupling agent containing siloxane and aziridine.
[0012] In one embodiment of the present invention, the solution plasma surface treatment comprises the following steps:
[0013] S1: Hexagonal boron nitride powder is mixed with a solution and placed in a container, which is connected to a plasma modification device with electrodes and is continuously stirred during the process;
[0014] S2: Wash and dry the treated particles obtained in S1.
[0015] In one embodiment of the present invention, the conductivity of the solution in S1 is 150-700 μS / cm; preferably, the solution is one or more of ammonia water, NaCl aqueous solution, and KCl aqueous solution.
[0016] In one embodiment of the present invention, there are multiple options for the electrodes of the plasma modification device described in S1, one of which is two parallel tungsten wires.
[0017] In one embodiment of the present invention, the voltage applied to the electrodes of the plasma modification device in S1 is a bipolar DC pulse waveform, preferably with an amplitude of 1.5-2.4 kV, a frequency of 70-80 kHz, and a pulse width of 0.5-2 μs.
[0018] In one embodiment of the present invention, the treatment time in S1 is 0.5-2h.
[0019] In one embodiment of the present invention, S2 is washed with ethanol.
[0020] In one embodiment of the present invention, S2 is dried at 60-80°C for 5-9h.
[0021] In one embodiment of the present invention, the modification of the silane coupling agent containing siloxane and aziridine comprises the following steps:
[0022] SS1: Mix the silane coupling agent with the solution and then hydrolyze it;
[0023] SS2: adding the hexagonal boron nitride powder surface treated by solution plasma into the mixed solution of SS1, treating and stirring for reaction;
[0024] SS3: Wash and dry the modified particles obtained in SS2.
[0025] In one embodiment of the present invention, the silane coupling agent described in SS1 contains siloxane and aziridine structures, and preferably the silane coupling agent is one or more of trimethoxysilane propyl aziridine, triethoxysilane ethyl aziridine, and triethoxysilane propyl aziridine.
[0026] In one embodiment of the present invention, the solution of SS1 is an ethanol-water solution.
[0027] In one embodiment of the present invention, the SS1 is hydrolyzed at 30-50°C for 1-3h.
[0028] In one embodiment of the present invention, the mass ratio of the hexagonal boron nitride powder modified by solution plasma described in SS2 to the silane coupling agent in the mixed solution of SS1 is 80:20-99:1.
[0029] In one embodiment of the present invention, the treatment time of SS2 is 20-60 minutes, and the stirring reaction time is 1-2 hours. The treatment method can be a conventional ultrasonic treatment method in the art.
[0030] In one embodiment of the present invention, the SS3 is cleaned with ethanol.
[0031] In one embodiment of the present invention, the SS3 is dried at 60-80°C for 8-12h.
[0032] Another object of the present invention is to provide a method for preparing a high thermal conductivity nylon composite material.
[0033] A method for preparing a high thermal conductivity nylon composite material, wherein the composite material is the high thermal conductivity nylon composite material mentioned above, or a high thermal conductivity nylon composite material of modified boron nitride obtained by the above preparation method, wherein the method prepares the composite material by extruding, molding, casting or one or more molding methods of modified boron nitride and nylon.
[0034] Compared with the prior art, the positive effects of the present invention are:
[0035] (1) The two-step modification increases the coverage of the coupling agent and improves its compatibility with nylon.
[0036] (2) The problem of h-BN being easy to agglomerate and having poor compatibility with the matrix is improved, so that it has better dispersion and stronger interfacial bonding in nylon, and the composite material can obtain higher thermal conductivity and mechanical strength at a lower BN addition amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a schematic diagram of the plasma modification device used in the present invention. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] Boron nitride: hexagonal boron nitride, Shanghai Chaowei Nanotechnology Co., Ltd., thickness 50nm, surface diameter 0.5-5 microns, average particle size 50nm;
[0040] Nylon 6, M1HC1-2, Guangdong Xinhui Meida Nylon Co., Ltd.;
[0041] Nylon 66: EPR27, Henan Pingdingshan Shenma Engineering Plastics Co., Ltd.;
[0042] Nylon 12: L2140, Evonik Industries;
[0043] Silane coupling agent: KH560, Kangjin New Materials;
[0044] Anhydrous ethanol: Aladdin, analytical grade;
[0045] NaCl aqueous solution: Aladdin, analytical grade;
[0046] 3-Aminopropyltriethoxysilane: Beijing Inokai Technology Co., Ltd., purity 99%;
[0047] 3-Aminopropyltrimethoxysilane: Beijing Inokai Technology Co., Ltd., purity 99%;
[0048] 3-Aminoethyltrimethoxysilane: Beijing Inokai Technology Co., Ltd., purity 99%;
[0049] Triethylamine: Beijing Inokai Technology Co., Ltd., purity 99%;
[0050] Toluene: Beijing Inokai Technology Co., Ltd., analytical grade;
[0051] 2,3-Dibromobutane: Beijing Inokai Technology Co., Ltd., purity 99%;
[0052] NMR: 1 H-NMR (Bruker ADVANCEⅢ400M).
[0053] Tensile properties: Instron tensile tester (INSTRON 5966) was used, the test method was in accordance with GB / T1040.1 and GB / T 1040.2, and the tensile speed was 20 mm / min;
[0054] Thermal conductivity: using a laser flash thermal conductivity meter (NETZSCH LFA467), the test method is in accordance with ISO 22007-4;
[0055] Heat resistance: A Mettler differential calorimeter (METTLER, TGA1) was used, the test method was in accordance with IS011358-1, and the heating rate was 10°C / min.
[0056] Twin-screw extruder: Equipment manufacturer: Nanjing Rubber and Plastic Machinery Factory, model SJSH-30, aspect ratio 36, diameter 30.
[0057] Injection molding machine: Equipment manufacturer Haitai Plastic Machinery Co., Ltd., model HTL90-F5B.
[0058] Example 1
[0059] Hydroxylation of BN: 500g of hexagonal boron nitride powder was mixed with 250ml of NaCl aqueous solution and placed in a beaker, and the amount of NaCl was adjusted so that the conductivity of the solution was 400μS / cm; the beaker was connected to the plasma modification device in the attached figure, and the electrodes were two parallel tungsten wires with a diameter of 1mm, and the distance between the two tungsten wires was 3.8mm. Except for the 1mm segment at the tip of the electrode, the rest were shielded by ceramic tubes or PTFE tubes. The voltage applied to the electrode was a bipolar DC pulse waveform with an amplitude of 1.5kV, a frequency of 80kHz, and a pulse width of 0.75μs. During the modification process, the magnetic stirrer was continuously stirred to disperse it, and the modification time was 1h. The beaker was placed in a water bath during the modification process to control the solution temperature below 70°C. The surface-treated BN particles were then washed 3 times with ethanol and dried at 80°C for 8 hours to obtain BN-1.
[0060] Preparation of coupling agent: In a 1L double-necked round-bottom flask equipped with a condenser, a nitrogen purge and a magnetic stirrer, 35.1g of 3-aminopropyltriethoxysilane, 41.7g of triethylamine and 240ml of toluene solution were placed and purged with nitrogen. Then 34.26g of 2,3-dibromobutane was added dropwise to the toluene mixture under an ice bath. The mixture was refluxed at 110°C for 6h and the solid was filtered out with diatomaceous earth. The solvent and volatiles were removed in a vacuum at 60°C and 20KPa to obtain an aziridine substance, the NMR characterization results of which were as follows: 1 HNMR(400MHz, CDCl3)0.58(t,2H),1.21(t,9H),1.39-1.43(m,2H),1.61(s,4H),2.46(t,2H),3.83(q,6H).
[0061] Coupling agent modification: Mix 5g of triethoxysilylpropylaziridine with pure water and anhydrous ethanol, with the molar ratio of coupling agent, ethanol and pure water being 1:5:3, and hydrolyze in a water bath at 40°C for 2h; add the surface-treated BN-1 into the mixed solution, with the mass ratio of BN-1 to silane coupling agent being 9:1, and after ultrasonic treatment for 30min, stir magnetically at 800r / min for 2h; wash it centrifugally with anhydrous ethanol for 3 times, and then dry it in a vacuum drying oven at 60°C and -0.1MPa for 8h.
[0062] Preparation of high thermal conductivity nylon composite material: the mass ratio of BN-2 to nylon 6 is 10:90. The molding method of the composite material is to extrude nylon and BN-2 through a twin-screw extruder. The extrusion temperature is 230℃-235℃-235℃-240℃-235℃ and the rotation speed is 300r / min. Finally, the dried pellets are injection molded into standard specimens by an injection molding machine. The temperatures of each section of the injection molding machine are set to 240℃, 245℃, 245℃, and 240℃.
[0063] Example 2
[0064] The steps of preparing a high thermal conductivity nylon composite material are as follows:
[0065] Hydroxylation of BN: 500g of hexagonal boron nitride powder was mixed with 250ml of NaCl aqueous solution and placed in a beaker, and the amount of NaCl was adjusted so that the conductivity of the solution was 400μS / cm; the beaker was connected to the plasma modification device in the attached figure, and the electrodes were two parallel tungsten wires with a diameter of 1mm, and the distance between the two tungsten wires was 3.8mm. Except for the 1mm segment at the tip of the electrode, the rest were shielded by ceramic tubes or PTFE tubes. The voltage applied to the electrode was a bipolar DC pulse waveform with an amplitude of 1.5kV, a frequency of 80kHz, and a pulse width of 0.75μs. During the modification process, the magnetic stirrer was continuously stirred to disperse it, and the modification time was 1h. The beaker was placed in a water bath during the modification process to control the solution temperature below 70°C. The surface-treated BN particles were then washed 3 times with ethanol and dried at 80°C for 8 hours to obtain BN-1.
[0066] Preparation of coupling agent: In a 1L double-necked round-bottom flask equipped with a condenser, a nitrogen purge and a magnetic stirrer, 28.41g of 3-aminopropyltrimethoxysilane, 41.7g of triethylamine and 240ml of toluene solution were placed and purged with nitrogen. Then 34.26g of 2,3-dibromobutane was added dropwise to the toluene mixture. The mixture was refluxed at 110°C for 6h and the solid was filtered out with diatomaceous earth. The solvent and volatiles were removed in vacuo at 60°C and 20KPa to obtain an aziridine substance, the NMR structure confirmation data of which are as follows: 1 HNMR(400MHz, CDCl3)0.58(t,2H),1.39-1.43(m,2H),1.61(s,4H),2.46(t,2H),3.55(s,9H).
[0067] Coupling agent modification: Mix 5g of trimethoxysilylpropylaziridine with pure water and anhydrous ethanol, with the molar ratio of coupling agent, ethanol and pure water being 1:5:3, and hydrolyze in a water bath at 40°C for 2h; add the surface-treated BN-1 into the mixture, with the mass ratio of BN-1 to silane coupling agent being 9:1, and after ultrasonic treatment for 30min, stir magnetically at 800r / min for 2h; wash it centrifugally with anhydrous ethanol for 3 times, and then dry it in a vacuum drying oven at 60°C and -0.1MPa for 8h.
[0068] Preparation of high thermal conductivity nylon composite material: the mass ratio of BN-2 to nylon 66 is 20:80. The molding method of the composite material is to extrude nylon and BN-2 through a twin-screw extruder. The extrusion temperature is 280℃-285℃-285℃-290℃-285℃, and the rotation speed is 300r / min. Finally, the dried pellets are injection molded into standard specimens by an injection molding machine, and the temperatures of each section of the injection molding machine are set to 280℃, 290℃, 290℃, and 290℃.
[0069] Example 3
[0070] The steps of preparing a high thermal conductivity nylon composite material are as follows:
[0071] Hydroxylation of BN: 500g of hexagonal boron nitride powder was mixed with 250ml of NaCl aqueous solution and placed in a beaker, and the amount of NaCl was adjusted so that the conductivity of the solution was 400μS / cm; the beaker was connected to the plasma modification device in the attached figure, and the electrodes were two parallel tungsten wires with a diameter of 1mm, and the distance between the two tungsten wires was 3.8mm. Except for the 1mm segment at the tip of the electrode, the rest were shielded by ceramic tubes or PTFE tubes. The voltage applied to the electrode was a bipolar DC pulse waveform with an amplitude of 1.5kV, a frequency of 80kHz, and a pulse width of 0.75μs. During the modification process, the magnetic stirrer was continuously stirred to disperse it, and the modification time was 1h. The beaker was placed in a water bath during the modification process to control the solution temperature below 70°C. The surface-treated BN particles were then washed 3 times with ethanol and dried at 80°C for 8 hours to obtain BN-1.
[0072] The preparation method of the coupling agent is consistent with that of Example 2.
[0073] Coupling agent modification: Mix 5g of trimethoxysilylpropylaziridine with pure water and anhydrous ethanol, with the molar ratio of coupling agent, ethanol and pure water being 1:5:3, and hydrolyze in a water bath at 40°C for 2h; add the surface-treated BN-1 into the mixture, with the mass ratio of BN-1 to silane coupling agent being 85:15, and after ultrasonic treatment for 30min, stir magnetically at 800r / min for 2h; wash it centrifugally with anhydrous ethanol for 3 times, and then dry it in a vacuum drying oven at 60°C and -0.1MPa for 8h.
[0074] Preparation of high thermal conductivity nylon composite material: the mass ratio of BN-2 to nylon is 30:70, the nylon used is a blend of nylon 6 and nylon 66, and the blending mass ratio is 3:7. The molding method of the composite material is to extrude nylon and BN-2 through a twin-screw extruder, the extrusion temperature is 230℃-235℃-235℃-240℃-235℃, the rotation speed is 300r / min, and finally the dried pellets are injection molded by an injection molding machine to form standard specimens, and the temperatures of each section of the injection molding machine are set to 240℃, 245℃, 245℃, and 240℃.
[0075] Example 4
[0076] Hydroxylation of BN: 500g of hexagonal boron nitride powder was mixed with 250ml of KCl aqueous solution and placed in a beaker, and the amount of KCl was adjusted so that the conductivity of the solution was 500μS / cm; the beaker was connected to the plasma modification device in the attached figure, and the electrodes were two parallel tungsten wires with a diameter of 1mm, and the distance between the two tungsten wires was 3.8mm. Except for the 1mm segment at the tip of the electrode, the rest were shielded by ceramic tubes or PTFE tubes. The voltage applied by the electrode was a bipolar DC pulse waveform with an amplitude of 2.0kV, a frequency of 75kHz, and a pulse width of 0.95μs. During the modification process, the magnetic stirrer was continuously stirred to disperse it, and the modification time was 1.5h. The beaker was placed in a water bath during the modification process to control the solution temperature below 70°C. The surface-treated BN particles were then washed 3 times with ethanol and dried at 80°C for 8 hours to obtain BN-1.
[0077] Preparation of coupling agent: In a 1L double-necked round-bottom flask equipped with a condenser, a nitrogen purge and a magnetic stirrer, 21.9g of 3-aminoethyltriethoxysilane, 27.8g of triethylamine and 240ml of toluene solution were placed and purged with nitrogen. Then 22.8g of 2,3-dibromobutane was added dropwise to the toluene mixture under an ice bath. The mixture was refluxed at 110°C for 6h and the solid was filtered out with diatomaceous earth. The solvent and volatiles were removed in vacuo at 60°C and 20KPa to obtain the aziridine substance.
[0078] Coupling agent modification: Mix 5g of triethoxysilane ethyl aziridine with pure water and anhydrous ethanol, with the molar ratio of coupling agent, ethanol and pure water being 1:5:3, and hydrolyze in a water bath at 50°C for 2h; add the surface-treated BN-1 into the mixed solution, with the mass ratio of BN-1 to silane coupling agent being 80:20, and after ultrasonic treatment for 30min, stir magnetically at 800r / min for 2h; wash it centrifugally with anhydrous ethanol for 3 times, and then dry it in a vacuum drying oven at 60°C and -0.1MPa for 8h.
[0079] Preparation of high thermal conductivity nylon composite material: the mass ratio of BN-2 to nylon 12 is 25:75. The molding method of the composite material is to extrude nylon 12 and BN-2 through a twin-screw extruder. The extrusion temperature is 210℃-215℃-215℃-220℃-225℃ and the rotation speed is 180r / min. Finally, the dried pellets are injection molded into standard specimens by an injection molding machine. The temperatures of each section of the injection molding machine are set to 220℃, 225℃, 230℃, and 225℃.
[0080] Example 5
[0081] Hydroxylation of BN: 500g of hexagonal boron nitride powder was mixed with 250ml of KCl aqueous solution and placed in a beaker, and the amount of KCl was adjusted so that the conductivity of the solution was 600μS / cm; the beaker was connected to the plasma modification device in the attached figure, and the electrodes were two parallel tungsten wires with a diameter of 1mm, and the distance between the two tungsten wires was 3.8mm. Except for the 1mm segment at the tip of the electrode, the rest were shielded by ceramic tubes or PTFE tubes. The voltage applied by the electrode was a bipolar DC pulse waveform with an amplitude of 2.2kV, a frequency of 70kHz, and a pulse width of 1.2μs. During the modification process, the magnetic stirrer was continuously stirred to disperse it, and the modification time was 2h. The beaker was placed in a water bath during the modification process to control the solution temperature below 70°C. The surface-treated BN particles were then washed 3 times with ethanol and dried at 80°C for 8 hours to obtain BN-1.
[0082] The preparation method of the coupling agent is consistent with that in Example 1.
[0083] Coupling agent modification: Mix 5g of triethoxysilane ethyl aziridine with pure water and anhydrous ethanol, the molar ratio of coupling agent, ethanol and pure water is 1:6:4, and hydrolyze in a water bath at 40℃ for 1.5h; add the surface-treated BN-1 into the mixed solution, the mass ratio of BN-1 to silane coupling agent is 95:5, after ultrasonic treatment for 30min, magnetically stir at 800r / min for 2h; centrifuge and wash it with anhydrous ethanol for 3 times, and then dry it in a vacuum drying oven at 60℃ and -0.1MPa for 8h.
[0084] Preparation of high thermal conductivity nylon composite material: the mass ratio of BN-2 to nylon is 35:65, the nylon used is a blend of nylon 6 and nylon 12, and the blending mass ratio is 2:8. The molding method of the composite material is to extrude nylon and BN-2 through a twin-screw extruder, the extrusion temperature is 230℃-235℃-235℃-240℃-235℃, and the rotation speed is 300r / min. Finally, the dried pellets are injection molded into standard specimens by an injection molding machine, and the temperatures of each section of the injection molding machine are set to 240℃, 245℃, 245℃, and 240℃.
[0085] Comparative Example 1
[0086] The method of Example 1 is referred to, except that: no solution plasma modification is performed, and other operations remain unchanged to obtain a high thermal conductivity nylon composite material.
[0087] Comparative Example 2
[0088] Referring to the method of Example 2, the difference is that no modification with a silane coupling agent is performed, and other operations remain unchanged to obtain a high thermal conductivity nylon composite material.
[0089] Comparative Example 3
[0090] Referring to the method of Example 2, the difference is that the coupling agent used is silane coupling agent KH560, and other operations remain unchanged to obtain a high thermal conductivity nylon composite material.
[0091] Table 1 Performance test results of embodiments and comparative examples
[0092]
Claims
1. A high thermal conductivity nylon composite material, characterized in that: The material includes modified boron nitride and nylon, and the mass ratio of nylon to modified boron nitride is 95:5-60:40; Wherein, the modified boron nitride is boron nitride that has been surface treated by solution plasma and modified by a silane coupling agent containing siloxane and aziridine; Preferably, the raw material boron nitride is hexagonal boron nitride; The nylon is one or more of nylon 6, nylon 66, nylon 610, nylon 1010, nylon 11, nylon 12, nylon 612, nylon 46, nylon 7, nylon 9, and nylon 13, preferably nylon 6 and / or nylon 66.
2. A method for preparing the modified boron nitride according to claim 1, characterized in that: The preparation method prepares modified boron nitride through two steps of treatment, wherein one step is solution plasma surface treatment and the other step is modification with a silane coupling agent containing siloxane and aziridine.
3. The preparation method according to claim 2, characterized in that: The solution plasma surface treatment comprises the following steps: S1: Hexagonal boron nitride powder is mixed with a solution and placed in a container, which is connected to a plasma modification device with electrodes and is continuously stirred during the process; S2: Wash and dry the treated particles obtained in S1.
4. The preparation method according to claim 3, characterized in that: The solution conductivity of S1 is 150-700 μS / cm; Preferably, the solution is one or more of aqueous ammonia, aqueous NaCl solution, and aqueous KCl solution; And / or, the voltage applied to the electrodes of the plasma modification device in S1 is a bipolar DC pulse waveform, preferably with an amplitude of 1.5-2.4 kV, a frequency of 70-80 kHz, and a pulse width of 0.5-2 μs; And / or, the treatment time in S1 is 0.5-2h.
5. The preparation method according to claim 3, characterized in that: S2 was washed with ethanol and dried.
6. The preparation method according to claim 2, characterized in that: The modification of the silane coupling agent containing siloxane and aziridine comprises the following steps: SS1: Mix the silane coupling agent with the solution and then hydrolyze it; SS2: Add the hexagonal boron nitride powder surface treated by solution plasma into the mixed solution of SS1 and stir to react; SS3: Washing and drying the modified particles obtained in SS2.
7. The preparation method according to claim 6, characterized in that: The silane coupling agent SS1 contains siloxane and aziridine structures, and the preferred silane coupling agent is one or more of trimethoxysilane propyl aziridine, triethoxysilane ethyl aziridine, and triethoxysilane propyl aziridine; And / or, the solution described in SS1 is an ethanol aqueous solution; And / or, the SS1 is hydrolyzed at 30-50° C. for 1-3 h.
8. The preparation method according to claim 6, characterized in that: The mass ratio of the hexagonal boron nitride powder modified by solution plasma described in SS2 to the silane coupling agent in the mixed solution of SS1 is 80:20-99:1; And / or, the treatment time of SS2 is 20-60 min, and the stirring reaction time is 1-2 h.
9. The preparation method according to claim 6, characterized in that: The SS3 was washed with ethanol and dried.
10. A method for preparing a high thermal conductivity nylon composite material, wherein the composite material is the high thermal conductivity nylon composite material according to claim 1, or a high thermal conductivity nylon composite material of modified boron nitride obtained by the preparation method according to any one of claims 2 to 9, wherein the method prepares the composite material by extruding, molding, or casting the modified boron nitride and nylon.
Citation Information
Patent Citations
Modified heat-conducting nylon composite material and preparation method thereof
CN109370204A
Preparation method of plasma modified hexagonal boron nitride / resin composite material
CN113105716A
Preparation method of nylon boron nitride nano composite material
CN116144017A
Boron nitride-resin composite material
JP2013203770A
Method for producing organic-inorganic composite material including boron nitride particle aggregate
JP2018053009A